2013
DOI: 10.4267/2042/50194
|View full text |Cite
|
Sign up to set email alerts
|

MEIS1 (Meis homeobox 1)

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Intriguingly, numerous reports have demonstrated that different molecular modulators are related to MEIS1 expression including TFs, miRNAs, and cellular metabolites (Aksoz et al, ). In addition, MEIS1 can modulate expression of involved genes in cell differentiation and proliferation such as HIF1/2, GATA1, CCND1/3, SOX3, and PBX1 (Torres‐Flores, ). It has been confirmed that MEIS1 is involved in progression of different malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, numerous reports have demonstrated that different molecular modulators are related to MEIS1 expression including TFs, miRNAs, and cellular metabolites (Aksoz et al, ). In addition, MEIS1 can modulate expression of involved genes in cell differentiation and proliferation such as HIF1/2, GATA1, CCND1/3, SOX3, and PBX1 (Torres‐Flores, ). It has been confirmed that MEIS1 is involved in progression of different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…MEIS1 (myeloid ecotropic viral integration site 1, OMIM: 601739), as an activator for the HOX members, forms heterodimer complex with HOX transcription factors to recruit either transcriptional co‐activator or co‐repressor in a DNA sequence‐dependent manner, modulating expression of target genes. Numerous TFs including PREP1, HOXA7, HOXA9, and CREB1 regulate MEIS1 expression in different normal tissues and several tumor cells (Torres‐Flores, ). MEIS1 has an essential role in regulation of stemness state of stem cells, transcription adjustment of self‐renewal genes, as well as involved genes in cell development and differentiation, playing an oncogenic role in several tumors (Dardaei et al, ; Rad et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein. Full-length MEIS1 consists of 390 amino acids and has a molecular weight of 43,016 da (6). MEIS1 contains a pre-B-cell leukemia homeobox (PBX)1 interaction domain, serine/threonine-rich domain, aspartic acid/glutamic acid-rich domain, poly-aspartic acid domain, homeodomain and transcriptional activation domain (10).…”
Section: Meis1 and Its Potential As A Cancer Therapeutic Target (Review)mentioning
confidence: 99%
“…MEIS1 is located between LOC729348 and LOC100507073 on chromosome 2p14, and contains the anonymous markers, D2S134 and NIB1519 ( 2 , 6 ). It consists of 13 exons and 137,360 bp ( 6 ).…”
Section: Molecular Biology Of Meis1mentioning
confidence: 99%
See 1 more Smart Citation